Kolofon S6 - Christoffersen, Erik Exe (Peripeti, 2024)
Peripeti © Peripeti and the writers Editors ofthis special issue: Erik Exe Christoffersen and Kathrine Winkelhom Lars Qvortrup’s and Theresa Bener’s articles were written in English. All other articles are translated from Danish by Kathrine Winkelhom Thanks to John Kendal for language revision and proofreading Thanks to Hotel Pro Forma for all photos This issue ofPeripeti is published with support from Lasson Andersens Fond Editorial board: Janicke Branth, Erik Exe Christoffersen (resp.) Michael Eigtved, Solveig Gade, Falk Heinrich, Kjersti Hustvedt, Jens Christian Lauenstein Led, Johan Holm Mortensen, Susanne Hjelm Pedersen, Thomas Rosendal Nielsen, Laura Luise Schultz, Mads Thygesen and Mette Tranholm Layout: Lho Brockhoff Cover photos: The One Who W hispers, 2012 (Claudi Thyrrestrup) Print: Werks Offset Edition: 400 ISSN: 1604-0325 Peripeti is published by Department ofDramaturgy, Aarhus University Address: Peripeti Department of Dramaturgy, Institute for Communication and Culture Aarhus University Langelandsgade 139 DK - 8000 Århus C Editor: aekexe@cc.au.dk www.peripeti.dk